2013
DOI: 10.1115/1.4023147
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of Novel Hybrid Composite Materials Using Taguchi Technique

Abstract: Novel Al-6061 hybrid composite materials with varying range of SiC particulate and constant weight percentage of B4C particulate and 1% of magnesium alloy were fabricated by the stir casting technique (liquid metallurgy route). The mechanical and tribological properties of the hybrid composites and that of Al-6061 unreinforced alloy were examined by a Rockwell hardness test machine, pin-on-disc test machine, and Optical Microscope and Scanning Electron Microscope (SEM). A plan of experiment generated through T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Uvaraj et al (Uvaraja et al, 2013) observed in his work that the introduction of B 4 C and SiC particulates to aluminum alloy shows an improvement in mechanical properties as compared Al6061 alloy, as these additives act as hindrances to the dislocation movement. Hybrid composites with Al6061-SiC+B 4 C demonstrate optimal combination to achieve high strength and hardness.…”
Section: Boron Carbidementioning
confidence: 99%
“…Uvaraj et al (Uvaraja et al, 2013) observed in his work that the introduction of B 4 C and SiC particulates to aluminum alloy shows an improvement in mechanical properties as compared Al6061 alloy, as these additives act as hindrances to the dislocation movement. Hybrid composites with Al6061-SiC+B 4 C demonstrate optimal combination to achieve high strength and hardness.…”
Section: Boron Carbidementioning
confidence: 99%
“…The most important stage in the design of experiment lies in the selection of control factors. In the present work, the impact of three parameters such as sliding velocity, normal load and filler content were studied using L 27 (3 13 ) Taguchi orthogonal design [23]. The experimental results were transformed into a signal-to-noise (S/N) ratio.…”
Section: Taguchi Experimental Designmentioning
confidence: 99%
“…Effect of the normal load and sliding speed on wear rate of two-body abrasive wear of aluminium reinforced polymer composite was investigated [13]. Recently, several studies on the wear behaviours of the hybrid composites were also performed [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%